PERAN PERKEMBANGAN BERBAHASA ANAK USIA DINI UNTUK MENGEMBANGKAN KEMAMPUAN REGULASI DIRI - Sriyanto, Agus; Arif, Muhammad; Arifin Ahmad, Zainal (JOURNAL J-MPI : JURNAL MANAJEMEN PENDIDIKAN, PENELITIAN DAN KAJIAN KEISLAMAN, 2023)
This study aims to show how self-regulation develops in children at Al-Amin Pandean Kindergarten who are between 4-5 years old. Children aged 4-5 years old were the focus of this qualitative case study research. The three stages of the Miles and Huberman model - data reduction, data display, and data verification - were used in the data analysis technique. Observation, interviews and documentation were used as data collection methods. The findings of the study show that the growth of self-control and language skills occur at the same time. How children regulate their thoughts, emotions and behavior can be greatly influenced by language. Through their interactions in the social world around them, language helps children internalize social structures and conventions. Children who interact with others have a greater awareness of others' opinions and expectations. Based on this research shows that language helps children's understanding of their own experiences and the experiences of others, it is through language that children apply this knowledge to their actions